Návrh informačního systému pro zájmové sdružení Těžební unie - Šanda, Luděk (Vysoké učení technické v Brně. Fakulta podnikatelská, 2011)
Tato bakalářská práce se zabývá návrhem informačního systému pro zájmové sdružení Těžební unie. Byla provedena analýza současné situace společnosti a důkladná analýza procesů spojených s problematikou týkající se zavádění informačního systému. Na základě výsledků byl vypracován návrh řešení, které bude možné použít na implementaci informačního systému ve společnosti Těžební unie.

This bachelor thesis is focusing on a creation of the design solution of the information system for the Czech Mining Association Těžební unie. This work provides the analysis of the current situation of the organisation as well as thorough analysis of all the process related to the implementation of the information system. The proposal of the final design solution was prepared on the base of the results; this solution is ready to be used for the implementation of the information system in the organisation Těžební unie.
Design of an Information System for the Těžební Unie Association
Keywords: Informace; data; informační systém; analýza procesů; datové modelování; funkční modelování; Drupal; Information; data; information system; process analysis; data simulation; functional simulation; Drupal